(untitled) (International Journal of Current Engineering and Technology, 2014)
The ever expanding information overload has caused a data glut. To navigate through that much amount of data we need to start using our visual senses more. That is , Visualizing information, so that we can see the patterns that matter and focus on the data that is important. In this field, Google has already made striding leaps by not only developing Google Charts, but also introducing the option of directly creating data visualizations on Google Maps using Fusion Tables and Google Spreadsheets . Using these tools , Google has effectively captured the market and has also made it very easy for beginners with minimum coding experience to create good data visualizations.